Baby driver - Wright, Edgar, 1974-; Elgort, Ansel, 1994-; Spacey, Kevin; James, Lily, 1989- (Sony Pictures Home Enter., 2017)
When a getaway driver is persuaded into working for a crime boss, he finds himself partaking in an operation that is doomed to fail.
Anamorphic wide screen 1.85:1.
Ansel Elgort, Kevin Spacey, Lily James, Eiza González, Jon Hamm, Jamie Foxx.
MPAA rating: R.
Keywords: Organized crime -- Drama; Crime films; Thrillers (Motion pictures).; Action and adventure films; Feature films; Fiction films